A volta dos filhos de dekassegui ao Brasil: escolarização, dificuldades e superação - Tanaka, Edna (2009)
The dekassegui is a long term discussing movement social phenomena and it is being target of many researches. Little by little, children that follow their parents became research theme as well, but the discussions are centered on those which are inserted on the japanese cultural context; there is no knowledge of any research about schooling way of returning children to Brazil. The propose of this research is studying the life story of a student, a dekassegui daughter, which returned to Brazil, on a theory perspective of Ciampa about identity constitution. The start step was identifying the registered at the Public State Scholl basic, of a Education Director, dekassegui s children, in order to qualifying the learning circumstances from the teachers, parents and/or responsible and students. From these surveys, a 11 years old student was chosen, registered at the third grade of State Scholl basic; all the difficulties faced by this child were ,,,,,, identified and studying all the identity transformations which occurred on these conditions, starting from the beginning of identity process is giving to the whole life. The qualificative approach was the option, using the life story in order to know the subject living, according to her own perspective, of her mother and teachers. Her experience as student in a japanese school é marked noticeable by the idiom difficulties and many problems, as a hardener bullying/ijime ( being attacked and humiliations), these situation lead the development of a timid and retracted player and health problems. On her returning to Brazil she meets at the public school a place which contributes that she tries metamorphose which make her stronger, changing in to a excellent student , to the teachers, a a friend to her friends, and above that recovering her health